Plectin, a novel regulator in migration, invasion and adhesion of ovarian cancer - Lanning Bai; Xueqian Qian; Hui Zhang; Yi Yuan; Xiaodong Cui; Min Cheng; Yangyang Han (Cell & Bioscience)
Abstract Background Ovarian cancer (OC) is one of the most prevalent gynecologic malignancies and exhibites the highest fatality rate among all gynecologic malignancies. The absence of an early diagnostic biomarker and therapeutic target contributes to an overall 5-year survival rate ranging from 30 to 50%. Plectin (PLEC), a 500 kDa scaffolding protein, has gained prominence in recent years due to its pivotal role in various cellular biological functions such as cell morphology, migration and adhesion, while the accurate role of PLEC in OC remains elusive. Results In this study, our findings demonstrate that PLEC exerts a positive influence on the progression of OC, encompassing cellular proliferation, migration, invasion, and adhesion both in vitro and in vivo. Conclusions The results providing new insights for the diagnosis and treatment in OC.